Remarks on a paper by Silverman - Vikramaditya Singh (International Journal of Mathematics and Mathematical Sciences)
We improve a result in Silverman's paper (1999) and answer a question he posed. We also consider a similar problem and obtain sufficient conditions for starlikeness.